Duodenal Varices: A Rare Manifestation of Portal Hypertension - Basak, Deepankar Kumar; Gomes, Richmond Ronald; Arfin, Md Samsul (Journal of Bangladesh College of Physicians and Surgeons, 2019)
We report a case of haematemesis & melaena due to ectopic varices located in the duodenum in a patient with NASH related CLD. Duodenal varices are a rare but potentially serious consequence of portal hypertension in the event of a bleeding. The etiology of duodenal varices can be classified into hepatic (e.g. cirrhosis) or extra hepatic (e.g. portal, splenic or superior mesenteric vein thrombosis). Endoscopic injection sclerotherapy (EIS) and endoscopic variceal ligation (EVL) are widely accepted as primary therapies for esophageal variceal bleeding whereas bleeding gastric fundal varices are usually treated with cyanoacrylate injection or shunt procedures. However there is no widely accepted treatment modality for duodenal varices. In the case presented, we used injection sclerotherapy with ethanolamine oleate, to obliterate varices and control bleeding. A short review on the etiology pathogenesis and management of ectopic varices is presented. J Bangladesh Coll Phys Surg 2019; 37(3): 156-159